Review articleBrachytherapy in Greater Poland Cancer Centre and in Poznan – the past and the presence - Skowronek, Janusz (Journal of Contemporary Brachytherapy, 2009)
The aim of this article is to describe the history of brachytherapy in Poznań from the beginning of 20th century. Among the most important medical and oncological institutions that were created in Poznań at the beginning of twentieth century were: Surgical Clinic of Poznań University (City Hospital, Poznań), Transfiguration of the Lord Hospital (Poznań) and Radiology Faculty of Poznań University (Poznań). After the World War II in 1953 at Garbary Street hospital three new departments were established: Surgery, Gynecology and General Departments. At that time, radium treatment was introduced to Gynecology and General Departments and it was applied in therapy till the early nineties, in spite of introducing LDR and HDR brachytherapy in seventies and eighties. The intense development of brachytherapy took place in late nineties, when brachytherapy treatment of non-gynecological tumors started. Today’s condition of brachytherapy at Greater Poland Cancer Centre (GCC) is presented in this article, too.